The Effect of Social Media Influencer on Brand Image, Self-Concept, and Purchase Intention - Hermanda, Atika; Sumarwan, Ujang; Tinaprillia, Netti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2019)
The purpose of the research was to discover how social media influencers influenced the brand image, self-concept and the purchase intention of cosmetic consumers. The social media influencers became the third party which provided information about cosmetic products to the social media audience. Those who had the same self-concept with the influencers often viewed them as role models in consumption. The increase of self-concept and brand image affected a consumer’s purchase intention. The research would implement the cross sectional design, with the data gathered through online questionnaires shared in social media accounts. The samples would be gathered using the convenience sampling technique, with respondents up to 219 people. The research implemented the purchase intention as the endogenous variable and social media influencers as the exogenous variable, as well as brand image and self-concept as the intervening variable. The analysis method that would be implemented was the Structural Equation Modeling (SEM), using the SmartPLS software. The research resulted in the significant negative influence of both social media influencer and self concept towards the purchase intention, in contrast with the brand image which had a significant positive effect.